Futures contracts for milk: how will they work? - Bob Cropp (Kansas Agricultural Experiment Station Research Reports, 1996)
The two new milk futures contracts offer dairy farmers and other buyers and sellers of milk and dairy products additional opportunities to manage price risk in an increasingly volatile milk price environment. The availability of these risk management tools is especially important given the market-oriented direction of federal dairy policy. The CSCE and CME contracts differ somewhat in their specifications. Potential hedgers will need to evaluate which offers the best opportunity to lock in prices. Hedgers also should look at the cheese and nonfat dry milk contracts in determining the most appropriate risk management strategy. Strategies may involve using more than one futures market. Key in any hedging decision is the basis, especially the predictability of the relationship between cash and futures prices. Hedgers should compare the alternative contracts in terms of which yields the most predictable basis given the type of hedge and the specific market conditions affecting their business.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Milk futures; Hedging